A cap 'n' collar protein isoform contains a selective Hox repressor function. - McGinnis, N.; Ragnhildstveit, E.; Veraksa, A.; McGinnis, W. (Development, 1998)
We have characterized a protein isoform (CncB) from the Drosophila cap 'n' collar locus that selectively represses cis-regulatory elements that are activated by the Hox protein Deformed. Of the three Cnc protein isoforms, CncB is expressed in a localized pattern in mandibular and labral cells of the head during mid-stages of embryogenesis. When CncB protein is absent or reduced, mandibular cells are homeotically transformed toward maxillary identities. This transformation is associated with persistent Deformed expression in anterior mandibular cells, since the Deformed autoactivation circuit is normally antagonized by CncB function in these cells. Heat-shock-induced ectopic expression of CncB in mid-stages of embryogenesis is sufficient to attenuate the activity of Dfd response elements in maxillary epidermal cells, but appears to have no effect in trunk epidermal cells on either the function or the response elements of other Hox proteins. CncB provides a mechanism to modulate the specificity of Hox morphogenetic outcomes, which results in an increase in the segmental diversity in the Drosophila head.